Analisis Strategi Pemasaran Menggunakan Marketing Mix (7P) dalam Meningkatkan Jumlah dan Loyalitas Anggota pada Koperasi Mitra Dhuafa Cabang Cikalong Wetan - Harry Nugraha; Adi Heryanto (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This study examines the implementation of the 7P marketing mix at Mitra Dhuafa Cooperative (KOMIDA), Cikalong Wetan Branch, and its role in improving membership growth and member loyalty. A qualitative case study approach was employed using observations, semi-structured interviews with five key informants, and document analysis. Data were validated through source and method triangulation and analyzed using thematic analysis. The findings reveal that people, process, and promotion are the most influential marketing mix elements affecting member loyalty and membership growth. Strong interpersonal relationships between field officers and members foster emotional loyalty, while limitations in service processes and digital promotion constrain organizational competitiveness. The study concludes that integrating all seven marketing mix elements with digital transformation is essential for strengthening member loyalty, attracting new members, and enhancing the long-term sustainability of microfinance cooperatives.